The Cognitive Dimension of Household Labor - Daminger, Allison (American Sociological Review, 2019)
Household labor is commonly defined as a set of physical tasks such as cooking, cleaning, and shopping. Sociologists sometimes reference non-physical activities related to “household management,” but these are typically mentioned in passing, imprecisely defined, or treated as equivalent to physical tasks. Using 70 in-depth interviews with members of 35 couples, this study argues that such tasks are better understood as examples of a unique dimension of housework: cognitive labor. The data demonstrate that cognitive labor entails anticipating needs, identifying options for filling them, making decisions, and monitoring progress. Because such work is taxing but often invisible to both cognitive laborers and their partners, it is a frequent source of conflict for couples. Cognitive labor is also a gendered phenomenon: women in this study do more cognitive labor overall and more of the anticipation and monitoring work in particular. However, male and female participation in decision-making, arguably the cognitive labor component most closely linked to power and influence, is roughly equal. These findings identify and define an overlooked—yet potentially consequential—source of gender inequality at the household level and suggest a new direction for research on the division of household labor.